Experimental Breeding of Rare Medicinal Plant Parkia roxburghii G. Don. - Siswoyo .; Ekarelawan .; Ervizal A.M Zuhud (Department of Forest Resources Conservation and Ecotourism - IPB University, 1993)
Kedawung (Ptukia roxburghii G. Don.) is a rare species of medicinal plants. Seeds of this plant are useful to relieve several types of stomach disorders, including cholera.The objective of this study is to examine the effect of several kinds of fertilizers, i.e. compost,